2011
DOI: 10.1186/1471-2458-11-862
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hyperglycaemia and the impact of high household income in transforming Rural China

Abstract: BackgroundThe prevalence of hyperglycaemia and its association with socioeconomic factors have been well studied in developed countries, however, little is known about them in transforming rural China.MethodsA cross-sectional study was carried out in 4 rural communities of Deqing County located in East China in 2006-07, including 4,506 subjects aged 18 to 64 years. Fasting plasma glucose (FPG) was measured. Subjects were considered to have impaired fasting glucose (IFG) if FPG was in the range from 5.6 to 6.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
4
15
0
Order By: Relevance
“…In high-income countries, the socio-economic status-diabetes relationship appeared to be negative, with the poor at greatest risk [3][4][5][6]16]. However, the strength of the association was less consistent in low-and middle-income countries [8][9][10]. However, the strength of the association was less consistent in low-and middle-income countries [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In high-income countries, the socio-economic status-diabetes relationship appeared to be negative, with the poor at greatest risk [3][4][5][6]16]. However, the strength of the association was less consistent in low-and middle-income countries [8][9][10]. However, the strength of the association was less consistent in low-and middle-income countries [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 23 case-control and cohort studies on socio-economic statusdiabetes association also revealed an increased risk for Type 2 diabetes for low socio-economic status groups based on education, occupation and income in high-income countries [17]. However, the strength of the association was less consistent in low-and middle-income countries [8][9][10]. We found that low income was associated with high odds of impaired fasting glucose and undiagnosed and diagnosed Type 2 diabetes, which is in accordance with the results from high income countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we selected the two-stage sampling procedure to collect samples. In the first stage, consider different income levels might affect the diet habits which can further affect the incidence of DM and PDM, we thus performed the population stratification based on the income levels (high level [> 1500 Renminbi {RMB}, middle level [1000 -1500 RMB], and low level [< 1000 RMB]) per capita per year (14,15). For each income level, we sampled one countryside from those countrysides around Guyuan city with the same income levels.…”
Section: Participantsmentioning
confidence: 99%